Analysis of Potential Development Housing and Settlement Area Using Geographic Information System (Case Study: Bojongsoang District, Bandung Regency) - Heryawan, Alifya Judo (Jurnal Geodesi Undip, 2022)
Bojongsoang Sub-district is one of the developing regions in Bandung Regency and includes a central service area based on Perda Nomor 27 Tahun 2007, also located in the boundary between Bandung Regency and Bandung City. According to strategic plan Bojongsoang Sub-district 2016-2021 have occurred movement land function and there is land use especially settlemet area that not suitable for the allocation area. Behind the problem there are several potentials become housing and settlement development areas there are, near jakarta-bandung high speed train stop location, near toll road accessibility, in the education area, several housing developments by developers, and the construction of shophouses by investors in housing for business. In addition, based on BPS data in 2019 the population of bojongsoang district from 2017-2019 increased by 4.015 people. In this research, the use of GIS for analysis how land potential suitable also how region potential become housing and settlement area with consideration land change in area study. The method used is fuzzy AHP with each weight, potential for flooding 27.3%, soil type 21.6%, water network 13.1%, slope 11.5%, road network 10%, educational facilities 8, 8%, health facilities 8.05%, and shopping centers 0.05%. The result land potential suitability housing and settlement with classification very suitable for 91,934 ha, suitable for 465,625 ha, quite suitable for 1291,109 ha, and less suitable for 977,524 ha. The result of land potential suitability housing and settlement to RTRW Bandung Regency 2016-2036 obtained 1295,333 ha suitable with RTRW and 1530,859 ha not suitable with RTRW. Bojongsoang subdistrict have potential area for housing and settlement and suitable with RTRW for 720,418 ha.